Comparison of Accuracy of Bracket Placement by Direct and Indirect Bonding Techniques using Digital Processing - An In-Vitro Study - Ravneet K Kalra; Sanjay Mittal; Chandrashekhar Gandikota; Vikas Sehgal; Rajiv Gupta; Zarina Bali (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Accuracy of bracket positioning is an essential part of successful orthodontic treatment. Ideally placed brackets help in treatment mechanics and improve consistency of the result. The current study compares the accuracy of bracket placement using direct and indirect bonding. Aim: The aim of the present study was to compare the accuracy of bracket placement by Direct and Indirect Bonding techniques using digitally captured and processed images. Materials and Methods: Brackets were bonded on thirteen sets of duplicated orthodontic models, six sets each for Direct and Indirect bonding and one set as predetermined “ideal” bonding. Ideal bonding was achieved through repeated revision of bonding till it was found to be ideal by a group of five experienced orthodontists. This is a standard procedure followed by historic studies for achieving ideal bonding. Accuracy of the bracket placement through direct and indirect method was compared against ideal bonding on three dimensions – bracket height, mesiodistal position and angulation. Digital processing was used to compare the twelve sets against the ideal bracket positioning. A student’s t-test was used to determine whether statistically significant differences existed among ideal and experimental groups. Results: Overall, the difference in accuracy in bracket placement between Direct and Indirect bonding was statistically insignificant. Indirect bonding yielded more accurate results on selected teeth (p≤0.05)- Bracket height on 34, mesiodistal position on 13 and 34 and angular placement on 44 and 14. Coefficient of variation for direct bonding was 0.855, 0.750, and 0.719 for bracket height, angulation and mesiodistal position respectively. Corresponding values for indirect bonding were 0.853, 0.799 and 0.445 respectively. Conclusion: Neither technique yielded ideal bracket placement. Overall, Indirect bonding was better in terms of accuracy more often (70% for vertical & 60% for horizontal positioning), but the difference was statistically insignificant indicating high variability. Hence, the advantage wasn’t consistent.